Agenesis of the Internal Carotid Artery Associated with Aortic Arch Anomaly in a Patient with Congenital Horner’s Syndrome - Dinç, Hasan; Alioglu, Zekeriya; Erdöl, Hidayet; Ahmetoglu, Ali (American Journal of Neuroradiology, 2002)
Summary: We report a rare case of agenesis of the left internal carotid artery (ICA) and an aortic arch anomaly that presented with ipsilateral congenital Horner’s syndrome. Digital subtraction angiography revealed left ICA agenesis shortly after its origin and anastomosis between the left maxillary artery and the supraclinoid segment of the left ICA. Aortography of the aortic arch revealed the right subclavian artery arising as the first branch of a left aortic arch, followed by a bicarotid trunk and a left subclavian artery. High resolution CT of the skull base revealed the absence of the left carotid channel, consistent with congenital agenesis of the ICA.